1999
DOI: 10.1074/jbc.274.25.17820
|View full text |Cite
|
Sign up to set email alerts
|

An Antagonist of cADP-ribose Inhibits Arrhythmogenic Oscillations of Intracellular Ca2+ In Heart Cells

Abstract: Oscillations of Ca2؉ in heart cells are a major underlying cause of important cardiac arrhythmias, and it is known that Ca 2؉ -induced release of Ca 2؉ from intracellular stores (the sarcoplasmic reticulum) is fundamental to the generation of such oscillations. There is now evidence that cADP-ribose may be an endogenous regulator of the Ca 2؉ release channel of the sarcoplasmic reticulum (the ryanodine receptor), raising the possibility that cADP-ribose may influence arrhythmogenic mechanisms in the heart. 8-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…1 Thus, it is possible that the estimates of SR Ca 2ϩ content changes using contraction measurements were influenced by effects of caffeine on myofilaments. Interestingly, in a more recent study, Rakovic et al 9 showed that 8-amino-cADPR reduced the frequency of spontaneous Ca 2ϩ waves, although cADPR itself enhanced the incidents of waves in cardiac myocytes exposed to ouabain. Spontaneous Ca 2ϩ waves are generally associated with increased SR Ca 2ϩ content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Thus, it is possible that the estimates of SR Ca 2ϩ content changes using contraction measurements were influenced by effects of caffeine on myofilaments. Interestingly, in a more recent study, Rakovic et al 9 showed that 8-amino-cADPR reduced the frequency of spontaneous Ca 2ϩ waves, although cADPR itself enhanced the incidents of waves in cardiac myocytes exposed to ouabain. Spontaneous Ca 2ϩ waves are generally associated with increased SR Ca 2ϩ content.…”
Section: Discussionmentioning
confidence: 99%
“…In guinea pig ventricular cells, the cADPR antagonists 8-amino-cADPR and 8-Br-cADPR have inhibited both depolarization-induced Ca 2ϩ transients and spontaneous Ca 2ϩ waves. 8,9 It has been further demonstrated that cADPR applied to the cytosol increases cell-average Ca 2ϩ transients and contractions 10 -13 and enhances the frequency of local Ca 2ϩ release events (ie, sparks) in both intact and permeabilized cardiac myocytes. 11,14 The effects of cADPR on Ca 2ϩ release are highly temperature dependent and relatively slow kinetically.…”
mentioning
confidence: 99%
“…Moreover, cADPR infusion was associated with spontaneous electrical and contractile activity, pointing towards the possibility that cADPR may exert arrhythmogenic activity in the heart (Rakovic et al 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Recent preliminary evidence shows that the synthesis of cADPR is enhanced by protein kinase A [25], raising the possibility that elevation of cADPR levels may be added to the variety of mechanisms leading to the positive inotropic actions of β-adrenoceptor agonists. It also appears that an excess of cADPR may increase the gain of CICR to such an extent that arrhythmogenic mechanisms are provoked [26].…”
Section: Figure 2 Time Course Of Effects Of Photoreleased Cadpr On Camentioning
confidence: 99%